2022
DOI: 10.1038/s41416-022-01966-5
|View full text |Cite
|
Sign up to set email alerts
|

FAK promotes stromal PD-L2 expression associated with poor survival in pancreatic cancer

Abstract: Background Pancreatic Cancer is one of the most lethal cancers, with less than 8% of patients surviving 5 years following diagnosis. The last 40 years have seen only small incremental improvements in treatment options, highlighting the continued need to better define the cellular and molecular pathways contributing to therapy response and patient prognosis. Methods We combined CRISPR, shRNA and flow cytometry with mechanistic experiments using a KrasG12Dp5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…By evaluating the association between pdcd1lg2 and OS or PFS, we found that high pdcd1lg2 expression was closely related to the deteriorated outcomes in BLCA, COAD, KIRP, LAML, LGG, MESO, PAAD, THCA, THYM, and UVM. These results are consistent with previous studies in bladder cancer ( 41 ), acute myeloid leukemia ( 42 ), and pancreatic ductal adenocarcinoma ( 43 , 44 ). However, some studies revealed different conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…By evaluating the association between pdcd1lg2 and OS or PFS, we found that high pdcd1lg2 expression was closely related to the deteriorated outcomes in BLCA, COAD, KIRP, LAML, LGG, MESO, PAAD, THCA, THYM, and UVM. These results are consistent with previous studies in bladder cancer ( 41 ), acute myeloid leukemia ( 42 ), and pancreatic ductal adenocarcinoma ( 43 , 44 ). However, some studies revealed different conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…To investigate whether FAK expression had any impact on the cancer cell response to IFNγ, we treated FAK-wt and FAK-/- cells in vitro with 10 ng/mL IFNγ and measured (1) the secretion of chemokines and cytokines, and (2) the expression of 770 immune-related genes. Forward-phase array profiling of tumour cell-secreted proteins identified a number of IFNγ-induced chemokines and cytokines likely to mediate paracrine signalling with the TME, several of which were downregulated in response to FAK loss and are protumourigenic, such as interleukin-6 (IL-6), 25 26 in the context of pancreatic cancer ( online supplemental figure 1A ). We performed NanoString nCounter digital gene expression analysis using the PanCancer Immune Profiling Panel, which identified subsets of IFNγ-induced genes that were upregulated in FAK-/- cells compared with FAK-wt cells ( figure 1E and online supplemental table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…30,31 The up-sPD-L2 profile observed in those post-COVID-ILD patients with lung structural and functional alterations could affect other cell subsets; reports indicated that high expression of PD-L2 is related to the presence of a macrophage subpopulation with anti-inflammatory and profibrotic functions called M2, which leads to the inhibition of T-cells, and in tumor models has been described that high expression of PD-L2 is associated with a poor prognosis. 32,33 Several studies suggest that M2 macrophages play a central role in the pathogenesis of fibrosis; for instance, M2 secretes connective tissue growth factors to mediate the proliferation and migration of fibroblasts. 34 Similarly, the depletion of the gen Mbd2 attenuates the TGF-β1 production and reduces M2 macrophage accumulation in lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%